Variation in the dielectric properties of freshly excised colorectal cancerous tissues at different tumor stages. Issue 7 (17th July 2017) - Li, Zhou; Wang, Weiwei; Cai, Zhai; Han, Shuai; Lin, Shiming; He, Linyun; Chen, Miaoliang; Pan, Dongyue; Deng, Guanhua; Duan, Song; Xin, Sherman Xuegang
Abstract : The study was designed to identify differences in the dielectric properties of ex vivo colorectal cancerous tissues at different tumor stages. To date, 130 freshly excised colorectal cancerous specimens underwent measurement of both relative permittivity and conductivity on the serosal and mucosal surfaces of the carcinoma nidus, and the mucosa of the surgical resection margin ranging from 50 to 500 MHz at the Larmor frequencies. Tumor node metastasis staging was determined according to pathological reports for each patient. There were statistically significant differences in the relative permittivity of both colorectal cancerous serosa and mucosa among stages ≤I, II, III, and IV and between stages ≤II and ≥III ( P  < 0.05) at most frequencies under 300 MHz; statistically significant differences in conductivity were also observed for most of the measured frequencies ( P  < 0.05). The significant differences in dielectric characteristics among tumor stages, especially between early and advanced stages, have value for selecting appropriate surgical strategies. The presented ex vivo data provide important information for magnetic resonance electrical properties tomography in vivo system because the frequencies of 64 MHz (1.5T) and 128 MHz (3T) are usually used in clinical settings. Bioelectromagnetics. 38:522–532, 2017. © 2017 Wiley Periodicals, Inc.